Telisik Pendidikan Anak Berkebutuhan Khusus: Telaah Konsep Pendidikan Cinta Kasih Menurut Jalaluddin Rumi - Saefullah, Muhamad (Pascasarjana IAIN Metro, 2025)
This article aims to explore the application of Jalaluddin Rumi’s concept of love-based education in the context of special needs education. This study employs a qualitative library research approach, analyzing primary sources from Rumi’s poetry and prose alongside secondary literature on Islamic education, Sufism, and special needs education. Data were examined using thematic analysis to identify key educational principles relevant to children with special needs. The findings reveal three major thematic outcomes: (1) love as a foundational ethical and spiritual principle that affirms the inherent dignity of children with special needs; (2) the educator–learner relationship as an empathetic and transformative engagement rather than a purely instructional interaction; and (3) education as a healing-oriented process that addresses emotional, social, and spiritual dimensions alongside academic development. The study highlights the practical implications of Rumi’s love-based educational philosophy for inclusive education, particularly in designing compassionate curricula, strengthening teachers’ empathetic competencies, and fostering supportive learning environments that accommodate the holistic needs of children with special needs. These findings contribute to the discourse on inclusive and humanistic educational approaches by offering a spiritually grounded framework for improving educational practices for children with special needs.